Trusted access scheme for intranet mobile terminal based on encrypted SD card - Jiyang LI; Pengyuan ZHAO; Zhe LIU (网络与信息安全学报)
In order to solve the problem of information security caused by illegal access of untrusted mobile terminals to intranet,a trusted access scheme for intranet mobile terminals based on encrypted SD card is designed.By using encrypted SD card as trusted hardware equipment,trusted start-up,integrity verification and Intranet trusted access of mobile terminal devices are realized.A secure storage and encrypted communication mechanism for data interaction between mobile terminal and Intranet is also created.The experimental results show that the scheme can effectively authenticate the security of mobile terminals without changing the basic architecture of mobile terminals,and to some extent protect the security of the Intranet environment.